Exploring entrepreneurial intentions, motivations and obstacles among final year students of UiTM Pahang / Musramaini Mustapha, Siti Aishah Mohamad and Ilyani Azer - Mustapha, Musramaini; Mohamad, Siti Aishah; Azer, Ilyani (Universiti Teknologi MARA Cawangan Pahang, 2012)
Nowadays, cultivating entrepreneurship has become a vital agenda in most countries. Entrepreneurship improves the standard of living in the society by creating job opportunities and contributing to the development of the country. The Ministry of Education (MOE) in collaboration with the Higher Learning Institutions has undertaken various efforts to shape the minds and intentions of students to become entrepreneurs. Therefore, it is crucial to investigate the level of intentions and motivations to be an entrepreneur among final year students. The sample of this study consists of 34 selected final year students from different courses of study who have attended Kursus Asas Keusahawanan (KAKS) organised by the Malaysian Academy of SME & Entrepreneurship Development (MASMED) of UiTM Pahang. The main objective of this paper is to explore a better understanding of the intentional and motivational factors that could inspire students toward entrepreneurship. In order to capture the true scenario toward entrepreneurship among them, the barriers to entrepreneurship are also considered. Therefore, this study also investigates the major obstacles to the development of future entrepreneurs among final year students. The results show that UiTM Pahang students have high intentions and motivations to be an entrepreneur, but the financial factor becomes the obstacle for them.